Effect of citric acid on structure and photochromic properties of WO3–TiO2–ZnO composite films prepared by a sol–gel method. Issue 10 (December 2015) - Chen, Weilong; Shen, Honglie; Zhu, Xiangrong; Xing, Zhengwei; Zhang, Sanyang
Abstract: In this study, WO3 –TiO2 –ZnO ternary composite films were successfully prepared by a sol–gel method using citric acid as the coordination agent. The effect of citric acid concentration in the precursor solutions on microstructure and photochromic properties of the composite films was characterized by Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM) and a UV–vis–NIR spectrophotometer. Firstly, the citric acid improves the stability of the precursors and help to prepare homogeneous composited films. However, SEM observation indicates that the aggregation of the particles in the films occurrs when the concentration of citric acid is above 0.6 M. Secondly, all the samples preprared from the precursors with ctric acid present much better photochromism than the films with none citric acid in the precusors. Especially, the sample corresponding to 0.6 M citric acid displays best photochromism. Finally, for the sample corresponding to 0.6 M citric acid, the more detailed photochromic properties such as time dependence of UV–vis absorption and the bleaching absorption spectra were further investigated.